COVID-19 serological survey-3 prior to second wave in Mumbai, India - Gajanan D Velhal; Jayanthi S Shastri; Daksha Shah; Sachee R Agrawal; Mangala Gomare; Deepika Mandar Sadawarte (Wolters Kluwer Medknow Publications, 2022)
Background: Subsequent to serosurveys 1 and 2 for COVID-19 carried out in three wards of Mumbai in July and August 2020, Municipal Corporation of Greater Mumbai conducted serosurvey 3 in March 2021. This was to identify the extent of exposure by testing specific IgG antibodies against COVID-19. Material and Methods: A cross-sectional study was conducted to find the prevalence of seropositivity in Mumbai, which included 10,197 samples belonging to patients visiting public dispensaries (slum population, 6006) and private (nonslum population, 4191) laboratories of Aapli Chikitsa network for blood investigations for non-COVID illnesses. The ward-wise number of unlinked anonymous samples from 24 wards was predecided by using probability proportionate sampling. The samples were collected using quota sampling technique as per predecided sample for each ward. These samples collected from nonimmunized individuals were tested for IgG antibodies at the Molecular Biology Laboratory of Kasturba Hospital for Infectious Diseases by chemiluminescence assay (CLIA) method. Results: The overall seropositivity was found to be 36.3% (41.6% in slum and 28.59% in nonslum population). It was more in city wards (38.28%) followed by western suburb (36.47%) and then eastern suburb wards (34.86%), matching with the proportion of cases in these wards during the study period. There was no significant difference in seropositivity among males and females and in different age groups. Conclusions: Seropositivity is higher in slum areas than nonslum areas. It has reduced in slum areas and increased in nonslum areas as compared to findings of serosurveys 1 and 2. This explains the detection of a greater number of cases from nonslum areas in the second wave. The average seropositivity of 36.3% justifies the necessity of immunization on a wider scale in the city. Periodic serosurveys are required at fixed intervals to monitor the trend of infection and level of herd immunity.